2018
DOI: 10.53318/msp.v8i01.1465
|View full text |Cite
|
Sign up to set email alerts
|

Facteurs favorisants les maladies diarrhéiques chez les enfants de 0 à 5 ans en commune II du district de Bamako au Mali

Abstract: Les diarrhées demeurent un véritable problème de santé publique par qu'elles constituent la deuxième cause de mortalité des moins de 5 ans. En milieu tropical, des études montrent plusieurs facteurs concourent à la fréquence et à la gravité des diarrhées. C'est dans un tel contexte que la présente étude des facteurs favorisants les maladies diarrhéiques chez les enfants de 0 à 5 ans en commune II du district de Bamako a été réalisée. Matériels et méthodes : Une étude transversale par sondage en grappe ayant co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 15 publications
2
4
1
Order By: Relevance
“…The majority of patients came from downtown Kamsar (89.76%), this would be explained not only by the proximity of the hospital, but also because downtown Kamsar has a large population that does not is not served by drinking water. The predominance of the housekeeping profession (61.09%) and mothers aged over 25 corroborates with that reported in Mali where the majority of mothers were housewives aged 20-29 years [9]. The uneducated mothers (76.79%) in our study was similar to that of Doutchi.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The majority of patients came from downtown Kamsar (89.76%), this would be explained not only by the proximity of the hospital, but also because downtown Kamsar has a large population that does not is not served by drinking water. The predominance of the housekeeping profession (61.09%) and mothers aged over 25 corroborates with that reported in Mali where the majority of mothers were housewives aged 20-29 years [9]. The uneducated mothers (76.79%) in our study was similar to that of Doutchi.…”
Section: Discussionsupporting
confidence: 90%
“…Mali [9]. The bacteriological examination of the stools is done by inoculating the stools on appropriate culture media [1].…”
Section: Discussionmentioning
confidence: 99%
“…Gentamicin and ciprofloxacin were among the most prescribed antibiotics in probabilistic antibiotic therapy in hospitals in 2021 in Mali [ 11 ]. For fluoroquinolones, the resistance rate was 55,7% in our study against 64.9% previously found in Bamako in a community setting with associated qnrA , qnrB , qnrS genes [ 7 ]. As the population was communal in the 2 studies, the difference in prevalence could be due to sampling bias.…”
Section: Discussioncontrasting
confidence: 48%
“…In our study, the multidrug resistance rate was 50%. The community study previously carried out in Bamako reported the detection of class 1, 2 and 3 integrons, genetic carriers of multi-resistance, in bacteria [ 7 ] showing a real need to strengthen molecular monitoring of resistance. Two meta analyzes presented variable rates of multidrug resistance, notably 66.3% in Asia [ 14 ] and 28% in countries with limited resources [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation